PENGARUH FINANCIAL DISTRESS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP INTEGRITAS LAPORAN KEUANGAN - Nopela Talu; Devi Wahyuningsih (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2023)
This study uses quantitative research, namely research that places more emphasis on objective measurement aspects of the integrity of financial statements. Source of data used in this research is secondary data. This study aims to determine how much influence the variables financial distress, leverage and company size have on the integrity of financial statements. The sampling method using a saturated sample is a sampling technique in which the entire population is used as a sample, so the number of samples used in this study is 81 samples. The analytical method used is panel data regression analysis. The results of the study show that financial distress and leverage have no significant effect on the integrity of financial statements, firm size has a significant effect on the integrity of financial statements.